Meningkatkan Hasil Belajar Siswa Dalam Pembelajaran IPA Kelas IV Melalui Metode Demonstrasi Di SD DDI Cabang Parigi - Nurdianti, Nurdianti (Jurnal Kreatif Online, 2018)
Especial problems in this research lowering result of learning student caused by use of method or inappropriate study media so that do not improve the result learn the student. as for this research target is to improve the result learn the student of class of IV SD DDI Branch the Parigi of through method Demonstrate the. this Research Device is executed in 2 cycle, with every cycle of through 4 phase: (1) planning, (2) execution, (3) of this and refleksi. Research. observation is executed in class IV with the student amount 24 people. Data collecting conducted with the final gift tes of action and observation sheet learn and student of every cycle. Data-Processing conducted with the analysis qualitative and quantitative. Result of research of execution of action showing that demonstration method can improve the result learn the student, this matter is visible from research result which menunjukan that at final action of cycle I complete student individually amount to 18 people from 24 student is so that obtained complete of klasikal 75% and absorpsion klasikal of equal to 74,56%. At final action of cycle II which complete individually 20 people is so that obtained complete of klasikal 83,3% and absorpsion klasikal 85,7%. Matter of this means study of cycle 11 have fulfilled the efficacy indicator with the minimum absorpsion klasikal 65% and complete learn the minimum klasikal 80 %. Pursuant to absorpsion klasikal and complete learn the klasikal ofÂ activity of cycle study II, inferential hence that study repair by using demonstration method can improve the result learn the student of subject IPA in class 1V SD DDI Branch Parigi. Keyword: Method Demonstrate the, Result Learn. IPA.